A REVIEW ON COMMON HAZARDS OF STEROIDS USE IN HYPERTENSION - KUMAR, KUNDAN; QURESHI, AHMED; HAVELIKAR, UJWAL; TIWARI, ABHISHEK; PATEL, AKHILESH (International Journal of Current Pharmaceutical Research, 2023)
Since hypertension raises the risk of cardiovascular disease and other consequences, it must be considered when deciding on a patient's course of treatment. Hypertension is the most dangerous adverse effect of corticosteroid use. Corticosteroid treatments, generally known as steroids or anti-inflammatory pharmaceuticals, are used to treat a variety of diseases. They differ from anabolic steroids, which some people often use illicitly to gain muscular mass. Despite being essential in the care of many inflammatory and immunologic illnesses, systemic corticosteroids carry a number of hazards. Osteoporosis, adrenal suppression, hyperglycemia, dyslipidemia, cardiovascular disease, Cushing's syndrome, psychiatric disorders, and immunosuppression are some of the more severe adverse effects of systemic corticosteroid therapy, particularly when taken in high dosages for lengthy periods of time. Using the most recent data as well as the authors' clinical expertise, this extensive study discusses these adverse occurrences and offers helpful advice for their prevention and management.